Distal hereditary motor neuropathy with vocal cord paresis: from difficulty in choral singing to a molecular genetic diagnosis. Issue 3 (19th January 2016) - Ingram, Gillian; Barwick, Katy E S; Hartley, Louise; McEntagart, Meriel; Crosby, Andrew H; Llewelyn, Gareth; Morris, Huw R
Abstract : Patients presenting with distal weakness can be a diagnostic challenge; the eventual diagnosis often depends upon accurate clinical phenotyping. We present a mother and daughter with a rare form of distal hereditary motor neuropathy type 7 in whom the diagnosis became apparent by initial difficulty in singing, from early vocal cord dysfunction. This rare neuropathy has now been identified in two apparently unrelated families in Wales. This family's clinical presentation is typical of distal hereditary motor neuropathy type 7, and they have the common truncating mutation in the SLC5A7 gene. Advances in genetic analysis of these rare conditions broaden our understanding of their potential molecular mechanisms and may allow more directed therapy.